The Effects of the empowerment program on HbA1C level of patients with type I diabetes mellitus at DM Clinic, Sakon Nakhon Hospital - Karun, Patsorn (Journal of Nursing and Health Sciences Nakhon Phanom University, 2025)
The quasi-experimental study employed a one-group pretest-posttest design to evaluate the effect of an empowerment program on glycosylated hemoglobin (HbA1C) levels among patients with type 1 diabetes mellitus. The study was undertaken in response to the increasing number of patients at Sakon Nakhon Hospital whose HbA1C levels exceed recommended thresholds, thereby elevating the risk of complications and treatment costs. A total of 34 patients with type 1 diabetes mellitus were enrolled. Research instruments comprised (1) the empowerment program and (2) data collection tools including a general information questionnaire and HbA1C laboratory results. Content validity of the instruments was confirmed with a validity index of 0.95. Reliability testing using Cronbach’s alpha yielded a coefficient of 0.91. Data were analyzed using paired t-test to compare pre- and post-intervention HbA1C levels. The findings demonstrated a statistically significant reduction in HbA1C levels following intervention (t = 3.904, p < .01). The mean HbA1C level decreased from 11.12 (SD = 2.80) prior to the program to 9.94 (SD = 2.28). After program participation. The results indicate that the empowerment program is effective in reducing HbA1C levels in patients with type 1 diabetes mellitus. Continued implementation and expansion of the program to other diabetes populations within the hospital’s catchment area are recommended to strengthen glycemic control and improve long-term clinical outcomes.